Correlation analysis of serum miRNA expression levels with the degree of macular edema in patients with retinal vein occlusion and its clinical implications - Lin, Jing; Zhao, Wei; Zang, Hanyi; Bao, Xin (Frontiers in Neurology, 2025)
ObjectiveTo investigate the correlation between serum microRNA (miRNA) levels and the degree of macular edema in retinal vein occlusion (RVO) patients.Methods180 RVO patients were divided into three groups based on macular edema severity: mild, moderate, and severe. Their serum miR-155-5p, miR-17-5p, and miR-375 levels were compared with 60 healthy controls. Pearson correlation analysis assessed the relationship between miRNA levels and clinical outcomes.ResultsmiR-155-5p levels were significantly higher in RVO groups compared to controls, while miR-17-5p and miR-375 levels were lower. Increased severity of macular edema correlated with higher miR-155-5p and lower miR-17-5p and miR-375 levels. After treatment, miR-155-5p levels decreased, while miR-17-5p, miR-375, and visual acuity improved. Correlation analysis showed that changes in miR-155-5p were negatively correlated with visual improvement and macular edema resolution, while miR-17-5p and miR-375 were positively correlated with these outcomes.ConclusionSerum miR-155-5p, miR-17-5p, and miR-375 levels are associated with macular edema severity in RVO. These miRNAs may serve as biomarkers for disease progression and prognosis, aiding personalized treatment strategies.